A construção do lugar académico dos estudos sobre esoterismo : a saída de uma quarentena - Mateus, Gabriel (2014)
During the last two decades we have witnessed the growth of a new field of knowledge after long periods of an «epistemological quarantine». According to Antoine Faivre, Western Esoteric can be defined as a «pattern of thought» with its roots in different forms of Greek philosophy, particularly Gnosticism, Hermeticism and Neoplatonism. Throughout the 20th century, the knowledge of these currents, particularly in the form they took during the Renaissance, has evolved to the point of being today and a well-defined discipline with academic curriculum. There are actually several universities with teaching and research programs in the field of Western Esotericism. This article seeks to give an overview of the state of the art of Western esotericism as an emerging academic discipline.